Evaluating the effects of different nutritional conditions on fruiting body development and extraction efficiency of Cordyceps militaris - Thao, Hoang Xuan; Hao, Nguyen Thị; Hoi, Truong Cong; Hai, Le Thanh; Trang, Le Thi Thuy; Nhi, Nguyen Thi Ngoc; Minh, Le Hoang Duy; Giang, Tran Van (Penerbit Universiti Kebangsaan Malaysia, 2025)
Cordyceps militaris is a valuable medicinal mushroom due to its bioactive components, especially cordycepin and adenosine, which have significant pharmacological activities. However, the yield and quality of fruiting bodies and their active compounds can vary greatly depending on the nutritional conditions during cultivation. This study aimed to determine the optimal culture medium and extraction procedure to enhance both biomass yield and bioactive compound content in C. militaris. The mushroom was cultivated under three nutritional conditions: Basal control medium, T1 medium supplemented with soybean powder and coconut water, and T2 medium supplemented with mineral salts (MgSO4 , K2 SO4 ) without soybean powder or coconut water. Growth performance, fruiting body morphology, and cordycepin/adenosine content were evaluated, followed by optimization of extraction efficiency using Box–Behnken design, taking into account extraction temperature, ethanol/mushroom ratio, and extraction time. T1 provided the most favorable conditions for the development of C. militaris fruiting bodies compared to the control group, including the indices stem length (9.82 ± 1.44 cm), diameter (0.83 ± 0.16 cm), number of fruiting bodies (185.88 ± 19.53), and weight (17.18 ± 2.73 g). HPLC analysis showed the highest content of cordycepin (337.93 ± 15.08 mg/100 g) and adenosine (394.51 ± 10.86 mg/100 g). Therefore, we used group T1 to evaluate the effects of temperature, ethanol/fungi ratio, and extraction time on extraction efficiency (17 treatments). The results showed that treatment 17, with the conditions of 60°C, ethanol/fungi ratio 20:1, 6 hr, gave the best extraction efficiency of 33.15%. These results showed that the addition of nutrients from soybean and coconut water and the factors (temperature, ethanol/fungi ratio, and extraction time) significantly affected both the biomass and bioactive compound content of C. militaris as well as the extraction efficiency, providing a basis for improving the large-scale cultivation and extraction process for functional food and pharmaceutical applications.